Loss of the chloride channel ClC-7 leads to lysosomal storage disease and neurodegeneration - Kasper, Dagmar (2005)
ClC-7 is a chloride channel of late endosomes and lysosomes. In osteoclasts, it may cooperate with H(+)-ATPases in acidifying the resorption lacuna. In mice and man, loss of ClC-7 or the H(+)-ATPase a3 subunit causes osteopetrosis, a disease characterized by defective bone resorption. We show that ClC-7 knockout mice additionally display neurodegeneration and severe lysosomal storage disease despite unchanged lysosomal pH in cultured neurons. Rescuing their bone phenotype by transgenic expression of ClC-7 in osteoclasts moderately increased their lifespan and revealed a further progression of the central nervous system pathology. Histological analysis demonstrated an accumulation of electron-dense material in neurons, autofluorescent structures, microglial activation and astrogliosis. Like in human neuronal ceroid lipofuscinosis, there was a strong accumulation of subunit c of the mitochondrial ATP synthase and increased amounts of lysosomal enzymes. Such alterations were minor or absent in ClC-3 knockout mice, despite a massive neurodegeneration. Osteopetrotic oc/oc mice, lacking a functional H(+)-ATPase a3 subunit, showed no comparable retinal or neuronal degeneration. There are important medical implications as defects in the H(+)-ATPase and ClC-7 can underlie human osteopetrosis.